PENGEMBANGAN BAHAN AJAR SISTEM PERSAMAAN LINEAR DENGAN MICROSOFT EXCEL DI SEKOLAH MENENGAH ATAS - Suhendra, Santoso (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2014)
This research is the development of interactive learning materials to produce a system of linear equations using Microsoft Excel, valid and practical, and potentially affect learning outcomes. The research was carried out in three stages: Preliminary analysis and design phase, which includes instructional materials, prototype, including the step of evaluation and revision, and field test. The results of data analysis concluded that this study has produced valid teaching materials and practical. Valid evidence from the results of some validation validator based on content, construct, and language. Practical evidence from observations of one-to-one and small group tests and obtained easy-to-use teaching materials according to the needs of students. In addition to a valid and practical, teaching materials also have potential effects on learning outcomes and activities of high school students seen from the assessment results of students during the field test. DOI: https://doi.org/10.22342/jpm.8.2.1867.44-56